The skeletal remains of the euryhaline sclerorhynchoid †Onchopristis (Elasmobranchii) from the 'Mid'-Cretaceous and their palaeontological implications. Issue 2 (1st February 2021) - Villalobos-Segura, Eduardo; Kriwet, Jürgen; Vullo, Romain; Stumpf, Sebastian; Ward, David J; Underwood, Charlie J
Abstract: We present the first known cranial remains of the fossil batoid † Onchopristis numidus . Based on two exceptionally well-preserved specimens collected from the 'Kem Kem Beds' (Albian–Cenomanian), south-east Morocco, an almost complete description of the rostral and cranial portions of the genus †O nchopristis is provided, together with new observations regarding the development and arrangement of the rostral denticle series for this genus. The comparison between the rostrum length of the specimens of † O. numidus with those of extant pristids, reveals a relatively large batoid species with an estimated total length between two and four metres. Overall, the cranial morphology of † Onchopristis resembles that of other sclerorhynchoids. Its robust hypertrophied rostrum, with the characteristic wood-like mineralization covering the inner layer of tessellate cartilage at the centre of the rostrum, in addition to the thick lateral layers of densely porous cartilage on the sides of the rostral cartilages, resembles that observed in † Ischyrhiza and † Schizorhiza, and differentiates † Onchopristis from other sclerorhynchoids (e.g. † Libanopristis, † Micropristis and † Sclerorhynchus ). Aiming to determinate the phylogenetic relations of † Onchopristis within sclerorhynchoids, a cladistic analysis was carried out based on the remains described here; its results suggest a new taxonomic arrangement within the sclerorhynchoids.